Bokimandalic psychology (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
Dependency is the consumption of healthy people without creating anything. This quality manifests itself in childhood, for example, in assigning homework or control work to someone else, in aggression towards other people's things. This quality causes theft, envy and other vices. A person can be compared to a pet in the backyard, you feed him once, and he hangs around you again, waiting for the next meal. But if this is the essence of the animal, then a person who is used to receiving help will begin to take it for granted and eventually turn into a carefree dependent.